2018
DOI: 10.1177/0733464818806834
|View full text |Cite
|
Sign up to set email alerts
|

Driving Status and Transportation Disadvantage Among Medicare Beneficiaries

Abstract: Transportation disadvantage may have important implications for the health, well-being, and quality of life of older adults. This study used the 2015 National Health Aging Trends Study, a nationally representative study of Medicare beneficiaries aged 65 and over ( N = 7,498), to generate national estimates of transportation modalities and transportation disadvantage among community-dwelling older adults in the United States. An estimated 10.8 million community-dwelling older adults in the United States rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…It is clear from each of these distinct but related frameworks that disparities in transportation access are deeply problematic. Indeed, the confluence of poor transportation resources and low access can lead to transportation-related social exclusion in which individual activity participation is curtailed and it becomes difficult to engage in the activities needed to lead a meaningful life, leading to impacts on health and quality of life (Duvarci et al, 2015;Lucas, 2012;Ryvicker et al, 2020). Those relying on public transit for most or all trips are at particular risk in the U.S. since transit service is often infrequent and inconvenient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is clear from each of these distinct but related frameworks that disparities in transportation access are deeply problematic. Indeed, the confluence of poor transportation resources and low access can lead to transportation-related social exclusion in which individual activity participation is curtailed and it becomes difficult to engage in the activities needed to lead a meaningful life, leading to impacts on health and quality of life (Duvarci et al, 2015;Lucas, 2012;Ryvicker et al, 2020). Those relying on public transit for most or all trips are at particular risk in the U.S. since transit service is often infrequent and inconvenient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Access to adequate transportation is a social determinant of health that is frequently overlooked in aging and public health research, as previous transportation-related studies have primarily focused on motor vehicle safety outcomes and indicators of driving abilities within aging samples [10]. While not uniquely a problem for PWH, previous research has shown a lack of adequate transportation has direct impacts on health-related outcomes in samples of adults living with chronic disease [7], patient retention in cardiac rehabilitation programs [11], access to care for those with traumatic brain injury (TBI) [12], and in U.S. Medicare beneficiaries [13], to name a few. Importantly, a lack of access to adequate transportation is not a newly discovered barrier for PWH.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the expected increase in older drivers (Sivak & Schoettle, 2016) will inevitably create a demand for more informal caregivers to meet the transportation needs of an older population transitioning to a non-driving status. An estimated 2.3 million older adult nondrivers who reside in the community report inadequate access to transportation (Ryvicker et al, 2020) that results in an increased reliance on family and friends. Although 80% of caregivers report providing transportation assistance, making it the most commonly reported instrumental activity of daily living (IADL; AARP & NAC, 2020), little is known about how assisting with transportation needs or the driving frequency of care recipients are related to the time spent caregiving.…”
Section: Introductionmentioning
confidence: 99%